2014
DOI: 10.1103/physreve.89.032201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into the impact of a liquid droplet onto a granular bed using three-dimensional, time-resolved, particle tracking

Abstract: (2014) 'Experimental investigation into the impact of a liquid droplet onto a granular bed using three-dimensional, time-resolved, particle tracking.', Physical review E., 89 (3). 032201.Further information on publisher's website:http://dx.doi.org/10.1103/PhysRevE.89.032201Publisher's copyright statement:Reprinted with permission from the American Physical Society: Physical Review E 89, 032201 c 2014 by the American Physical Society. Readers may view, browse, and/or download material for temporary copying pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 38 publications
2
52
1
Order By: Relevance
“…The fraction of energy for ejecting particles is then E eject ≡ f · E, with f < 1 automatically satisfied by construction. E eject is consistent with recent experiments that estimate the momentum of ejected particles (21). Finally, an energy scaling argument similar to that used for solid-sphere impacts can be applied: instead of E, E eject lifts granular particles in a crater of volume V c to a height determined by d c , i.e., E eject ≈ ϕρ sand V c gd c , where ϕ = 0:60 is the volume fraction of the bed and ρ sand is the particle density.…”
Section: Theory and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The fraction of energy for ejecting particles is then E eject ≡ f · E, with f < 1 automatically satisfied by construction. E eject is consistent with recent experiments that estimate the momentum of ejected particles (21). Finally, an energy scaling argument similar to that used for solid-sphere impacts can be applied: instead of E, E eject lifts granular particles in a crater of volume V c to a height determined by d c , i.e., E eject ≈ ϕρ sand V c gd c , where ϕ = 0:60 is the volume fraction of the bed and ρ sand is the particle density.…”
Section: Theory and Discussionsupporting
confidence: 78%
“…Here, d c is the depth of crater, defined as the vertical distance between the rim and the bottom floor of the crater. Previous studies reported the depth of crater in the presence of granular residues (17,21), which, however, does not reflect the true bottom of a crater underneath the granular residues. Here, to detect d c without the optical obstruction of granular residues in the center of crater, we focus on the range of E where the liquid marble bounces off the surface (Fig.…”
Section: Results: Morphology Of Impact Cratersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, detachment by raindrop impact is a relatively inefficient process. Long et al (2014) have estimated that only 2-4 % of raindrop-impact momentum is transferred to movement as splash. As shallow, surface flows start to occur, the effects of rainfall and flow energy initially combine (Parsons et al, 1993), but then as the flow depth increases the energy reaching the bed from raindrop impact exponentially decreases (Torri et al, 1987) so by then, flow detachment dominates (Parsons et al,.…”
Section: Spatial and Temporal Feedbacks Between Sediment-detachment Amentioning
confidence: 99%
“…It is only in the last decade, that drop impact on sand started to draw the attention of physicists, with studies focused on rain showers [12,13] or single drop impact [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%